PENAL MEDIATION THROUGH THE CUSTOMARY TEPUNG TAWAR TRADITION IN MEDICAL MALPRACTICE RESOLUTION - Junaidi Junaidi (Cepalo)
Medical malpractice refers to treatment by doctors or healthcare professionals that deviates from established standards or violates legal and ethical norms. However, Article 310 of Law Number 17 of 2023 on Health lacks clarity, as it does not explicitly define mediation as an alternative dispute resolution mechanism or address the resolution of criminal offences arising from medical malpractice. This research aims to propose penal mediation through the tepung tawar tradition as a means to achieve justice and introduce innovative reforms in criminal law. Using a normative juridical approach, which relies on library research and secondary legal sources, this research explores the tepung tawar tradition as a model for resolving medical malpractice cases through penal mediation, enabling amicable settlements that eliminate both civil and criminal liability. Therefore, harmonizing customary law with formal legal frameworks is essential to ensuring broader and more equitable justice in addressing medical malpractice in Indonesia.